List Ojca Świętego Jana Pawła II do Episkopatu Kościoła Katolickiego na 1800 rocznicę I Soboru Konstantynopolitańskiego i na 1550 rocznicę Soboru Efeskiego - Paweł II, Jan (Vox Patrum, 2020)
Apostolic Letter of His Holiness John Paul ii to the bishops of the Catholic Church for the 1600th anniversary of the first Council of Constantinople and the 1550th anniversary of the Council of Ephesus.